Présentation de la discussion sur le figement linguistique et les trois fonctions primaires (prédicats, arguments, actualisateurs) - Mejri, Salah (Neophilologica, 2011)
This issue, devoted to lexical freezing, aims to be innovative because it approaches this question from the perspective of the three primary functions. As this type of function is not yet known in the linguistic literature, we will present it after recalling the role that freezing plays in the general economy of linguistic systems and showing the relevance of the intersection of the notion of freezing with that of primary functions. After this presentation, we will try to identify the theoretical issues that are implicit in the contributions of this issue.